Answers

2016-04-27T22:01:03+08:00
Let x =  larger integral   &  y =smaller integral
   thus         x  -    y       =   9                 &     5y =  3x + 9

                   3x   -  3y     =      27     / equivalent equation
                   3x   - 5y      =      -9
                            2y      =      36

                             y    = 18
                     x - 18  =   9    / substitute in first equation
                     x  =    27
                     the integrals  are      18  & 27
0